(untitled) (Development Service Industry Management, 2023)
In the food security strategies of the post-Soviet countries, different priorities have been set: from a focus on "self-sufficiency" to financial and technical support for producers, food quality, promotion of exports and improvement of infrastructure. However, relatively little attention has been paid to strategies aimed at promoting a balanced and healthy diet, which will contribute to reducing the risk of overweight, obesity and related diseases. In a peaceful existence, national and regional policies, strategies and programs should more convincingly target the quality of food consumed and dietary habits as the most pressing issues facing countries. For Ukraine, as well as for many other countries of the world, unfortunately, another one is added to the traditional obstacles on the way to ensuring food security - war. Therefore, the purpose of the study is to substantiate the strategic directions for strengthening the food potential of Ukraine. Since Ukraine belongs to the group of "triple burden" countries (undernourishment, deficiency of micronutrients and overeating), we focused on substantiating strategic directions in the field of building food potential to solve the specified problem. As a result of the research, based on the positive practices of the implementation of strategies in various post-Soviet countries and taking into account the problems that Ukraine needs to solve in the field of food potential formation, it is proposed to apply the following policy measures in the field of nutrition in Ukraine: changing the content of food products; fiscal measures; nutrition education; food safety; nutrition labeling of products; food aid policy. It is expedient to implement certain policy measures in the field of nutrition in Ukraine with the help of the following tools: promotion of dietary diversity and diversification of food production; active learning of the rules of proper nutrition; campaigns to inform the population about a healthy lifestyle. We consider three components to be the main strategic directions for strengthening Ukraine’s food potential: leveling the negative impact of extreme climatic events; stimulation of general economic growth; settlement of conflicts, ensuring peace. The last direction currently needs development to solve.